Environmental-psychological dissection of disease narratives in The Dream of the Red Chamber: Social stress theory and the reflection of individual psychology - TEOH HOOI SEE; YUSHAN XIE (Environment and Social Psychology, 2026)
Research examining this work shows limited analysis using data for illness accounts. The study develops a model that shows relationships between social factors and individual responses. This model uses theory examining factors in society and approaches that consider individual patterns. The study examines six main figures in the work. Analysis using SPSS assesses measures that include likelihood of illness and levels of stress showing peaks. Results indicate that particular factors in society relate to particular forms of illness. This relationship shows correspondence rates that exceed eighty-six percent. Findings reveal that support from others provides significant effects for individuals showing particular response patterns. These individuals demonstrate patterns of holding responses within. Data show that stress occurs before illness becomes more severe. This relationship between factors shows correlation measures of point seven nine and higher. Analysis indicates that severity follows a pattern showing initial stability. This pattern then reveals sharp increases in severity. Following these increases, the pattern shows gradual decreases over time. The findings suggest that conditions in society operating within structures of authority transform into individual illness. This process occurs through social and individual factors that operate between society and the individual. The approach provides a model using data for examining works from the past. This model allows analysis that combines different approaches to interpretation.